Stressors identified for the patient submitted to Myocardial Revascularization and Percutaneous Transluminal Coronary Angioplasty - preview note. - Graciele Fernanda da Costa Linch; Laura de Azevedo Guido; Luiza de Oliveira Pitthan (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
It is a research project that is being developed at Santa Maria University Hospital (HUSM), aiming to identify the prevalent stressors to patients which suffer of heart disease. To collect data it will be used a questionnaire to identify the patients on pre procedure, to characterize the population; and the Intensive Care Unit Environmental Stressor Scale (ICUESS) on post procedure. After indentifying the stressor on these patients' perspective, it will be possible to organize nursing protocols that will allow an assistance adequation to the real patients' necessities, making the environment more appropriated, pleasant, minimizing the stressors effects.